2012
DOI: 10.1152/ajpendo.00310.2011
|View full text |Cite
|
Sign up to set email alerts
|

Insight into molecular pathways of retinal metabolism, associated with vitellogenesis in zebrafish

Abstract: Levi L, Ziv T, Admon A, Levavi-Sivan B, Lubzens E. Insight into molecular pathways of retinal metabolism, associated with vitellogenesis in zebrafish. Am J Physiol Endocrinol Metab 302: E626 -E644, 2012. First published December 28, 2011; doi:10.1152/ajpendo.00310.2011Retinal is the main retinoid stored in oviparous eggs of fish, amphibians, and reptiles, reaching the oocytes in association with vitellogenins, the yolk precursor proteins. During early presegmentation stages of zebrafish embryos, retinal is met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 90 publications
3
53
0
Order By: Relevance
“…We also confirmed vtg4 up-regulation in the liver by in situ hybridization (Figure S5). As a member of the vtg family, vtg4 has been investigated in the adult liver [23,30]; however, no such study has been performed for developing embryos. …”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed vtg4 up-regulation in the liver by in situ hybridization (Figure S5). As a member of the vtg family, vtg4 has been investigated in the adult liver [23,30]; however, no such study has been performed for developing embryos. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to retinol, certain carotenoids can be converted into vitamin A in many species of animals, although it is unclear if all insectivores have the ability to convert beta-carotene to retinol (Bender, 2002;Levi et al, 2012;McComb, 2010;Olson, 1989). Carotenoids are found at high levels in many species of wild insects, whereas captive-bred insects contain significantly lower quantities (Eeva et al, 2010;Finke, 2013;Isaksson and Andersson, 2007;Oonincx and van der Poel, 2011).…”
Section: Vitamin Amentioning
confidence: 99%
“…Expression studies of apoea (Raymond et al, 2006) and apoeb (Pujic et al, 2006) revealed expression in the developing retina and yolk syncytial layer. Furthermore, apoeb has also been observed in microglial cells (Veth et al, 2011), developing fins and epidermis (Monnot et al, 1999; Tingaud-Sequeira et al, 2006), regenerating fin tissue (Monnot et al, 1999), macrophages (Lien et al, 2006), liver, intestine, and ovary (Levi et al, 2012). …”
Section: Using the Zebrafish To Investigate Other Aspects Of Alzheimementioning
confidence: 99%